Strain-promoted perpendicular magnetic anisotropy in Co-Rh alloys - DEĞER, CANER; YAVUZ, İLHAN (AMER INST PHYSICS, 2020)
We report on a comprehensive experimental, numerical, and computational investigation on the concentration dependence of the structural/magnetic properties of Co-Rh alloy films. A sizable perpendicular magnetic anisotropy is achieved by controlling the lattice strain via the Co content. Within the 30-40% range of Co concentrations, an experimental effective magnetic anisotropy on the order of 100kJ/m(3) and a computational uniaxial magnetic anisotropy energy of 567 mu eV/atom have been observed. First-principles calculations revealed that the lattice strain promotes a strong d-orbital degeneracy near the Fermi level for 40% of Co concentration, leading to an enhanced magnetic anisotropy energy.
Keywords: ROOM-TEMPERATURE; THIN-FILMS; BEHAVIOR; PD/CO